Use of Blockchain in Crypto-Currency to secure cloud forensic trails (Trinity Journal of Management, IT & Media (TJMITM), 2022)
European Union (EU) law i.e. GDPR, which came into existence on May 25th 2018 that produces difficult challenges to most of the cloud users. Distributed network operators are capable to reveal more observation comparison to the cloud-based users. Many cloud customers can be absolutely now no longer capable of exhibit compliance with the current regulation, therefore revealing themselves to doubtlessly big fines following to May 25th. As we know the usage of a crypto-currency is turning into a universal fact, obtaing greater interest from mass media, commercial initiative entrepreneurs, monetary plus administration establishments. We spotlight to the functioning hazard as well as the marketplace hazard linked to crypto moneys. We review the literature findings on the crypto currencies to demonstration the part of crypto money as an article of trade, exchange or, a hypothetical venture in making divergence philosophy of portfolio. As we know assaults on cryptocurrencies even getting mileage therefore the practice of such expertise up to which level might render businesses consuming this expertise for the fulfilment of GDPR. To forte of this technique, we study Blockchain i.e. distributed ledger expertise to address the cloud forensic hassle. This paper focuses on the good points and bad points of the (blockchain-bitcoin) technique, in search of to discover weaknesses and capacity advantages presented against the further useful prices/potential resource concerned, also could be considered as making safe cloud forensic hassles.
Keywords: Cloud; issue of forensic; General Data Protection Regulation; blockchain; crypto-currency; bitcoin technology